Деякі питання, пов’язані із застосуванням назв професійних кваліфікацій в освітньо-професійних програмах «Логопедія» другого (магістерського) рівня вищої освіти - Мицик, Ганна Михайлівна; Пришляк, Михайло (ДДПУ iменi Iвана Франка, 2021)
У статті досліджено існуючі тенденції використання закладами вищої освіти в освітньо-професійних програмах спеціальності 016 Спеціальна освіта, спеціалізація 016.01 – логопедія другого (магістерського) рівнів вищої освіти назв таких професійних кваліфікацій як «вчитель-логопед» та «логопед». Вказано на відсутність належної уваги з боку науковців до питань, пов’язаних із застосуванням назв професійних кваліфікацій в освітніх (освітньо-професійних, освітньо-наукових чи освітньо-творчих) програмах. Констатовано, що, відповідно до існуючої нормативно-правової бази, професії вчителя-логопеда за дипломом має відповідати освітня кваліфікація магістра, тоді як професії логопеда – освітня кваліфікація бакалавра. Здійснено порівняльний аналіз змісту діяльності вчителя-логопеда та логопеда, встановлені притаманні їй загальні та відмінні ознаки. Щодо відмінностей зазначено, що вони простежуються в підпорядкованості закладів, в яких працюють вчитель-логопед і логопед, різним відомствам (Міністерству освіти і науки України та Міністерству охорони здоров’я України), в контингенті, з яким доводиться працювати вчителю-логопеду та логопеду, характері захворювань, які стали причиною порушення мовлення у їхніх підлеглих. З іншого боку визнано, що за змістом здійснюваних робіт, рівня знань, які при цьому вимагаються, є всі підстави вбачати в них фахівців одного рівня підготовки, а саме другого (магістерського) рівня. Висловлені пропозиції, реалізація яких дозволила б закладам вищої освіти на законних підставах включати до орієнтованого переліку професійних кваліфікацій, зазначених в освітньо-професійній програмі спеціальності 016 Спеціальна освіта, 016.01 спеціалізація – логопедія другого (магістерського) рівнів вищої освіти, професійну кваліфікацію «логопед», присвоювати її здобувачам, які успішно виконали зазначену освітньо-професійну програму.
The existing trends in the use by universities in educational and professional programs of specialty 016 Special education, specialization 016.01 – speech therapy of the second (master) levels of higher education of the names of such professional qualifications as «teacher-speech therapist» and «speech therapist» were examined in the article. The lack of due attention of scientists to issues related to the use of the names of professional qualifications in educational programs (educational and professional, educational and scientific or educational and creative) is indicated. It was stated that, in accordance with the existing regulatory framework, the diploma-based speech therapist’s profession should correspond to the educational qualification of a master, while the speech therapist’s profession should correspond to the educational qualification of a bachelor. A comparative analysis of the content of the activity of a teacher-speech therapist and a speech therapist was carried out, common and distinctive features inherent in it were established. Regarding the differences it was noted it can be traced in the subordination of the institutions in which a teacher-speech therapist and a speech therapist work to various departments (the Ministry of Education and Science of Ukraine and the Ministry of Health of Ukraine); in the contingent with whom a teacher-speech therapist and a speech therapist have to work, the nature of the diseases that caused the speech impairment of their subordinates. On the other hand, one was admitted that in terms of the content of the work being carried out, the level of knowledge that is being obtained at the same time, there is every reason to see in them specialists of one level of training, and of another (master’s) level. Proposals that were expressed, the implementation of which would allow institutions of higher education on a legal basis to be included in the oriented List of professional qualifications specified in the educational and professional program of specialty 016 Special education, 016.01 specialization – speech therapy at other (master’s) levels of the higher education, professional qualification «speech therapist» its applicants who have successfully completed the specified educational and professional program.
Keywords: educational-professional program; education qualification; professional qualification; teacher-speech therapist; speech therapist; освітньо-професійна програма; освітня кваліфікація; професійна кваліфікація; вчитель-логопед; логопед